A Dual Grid Level Set Method based study on similarity and difference between interface dynamics for surface tension and radial electric field induced jet breakup. (12th July 2016) - Lakdawala, Absar M.; Sharma, Atul; Thaokar, Rochish
Abstract: The present work on radial electric field induced jet breakup is an extension of our recent work (Lakdawala et al., 2015b ) on surface tension force induced jet breakup . A Dual Grid Level Set Method (DGLSM) based numerical study on the non-linear breakup of viscous liquid jets immersed in another viscous fluid under radial electric field is carried out in this work. This leads to a better understanding of the mechanism of electrocapillary jet breakup and subsequent formation of primary and satellite drops, due to the temporal growth of surface perturbation. The influence of the electrical Bond number ( B oe ) and Reynolds number ( Re ) on the growth rate, the breakup time, the volume of the primary and satellite drops, and the charge of both primary and satellite drops is analyzed. An excellent agreement of the present numerical with the published analytical results is obtained for different Reynolds numbers ( Re = 10, 100 ), wave numbers ( 0 < k ≤ 1 ) and electric Bond number ( 0 < B oe < 4 ) . The results show that electrostatic stresses stabilize the long waves and destabilize the short waves which are in accord with linear stability theory: confirming the robustness of our DGLSM method in simulating two-phase electrohydrodynamic flow. The results indicate that nonlinear contribution from the electrostatic force is very important in analyzing the mechanism of satellite formation. The numerical results reveal that the satellite formation as well as the breakup time is affected significantly when the effect of conduction is weak. For large conduction, the evolution of the thread is close to those obtained for a perfectly conducting core fluid. Finally, we numerically show that the local dynamics may be altered when the conduction is weak compared to the perfect conductor limit. Abstract : Highlights: DGLSM is demonstrated as powerful tool to characterized electrohydrodynamic flow simulations. The non-linear jet dynamics under radial electric field is studied. The formation of satellite and sub-satellite in electrocapillary jet breakup is explained. Effect of electrification on growth rate, breakup time, charge and diameter of drop is evaluated. The dynamics of poorly conducting jet under radial electric field is studied.